The talking cat and other stories of French Canada - Carlson, Natalie Savage; Duvoisin, Roger 1900-. (New York Harper, 1952)
Seven tales that helped comprise the evenings' entertainment for French Canadians before radio and television.
Keywords: French Canadians -- Folklore; Folklore -- Canada